2022
DOI: 10.1038/s41598-022-15741-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between organochlorine pesticides and nonalcoholic fatty liver disease in the National Health and Nutrition Examination Survey 2003–2004

Abstract: While endocrine disruptors are emerging as a cause of nonalcoholic fatty liver disease (NAFLD), little is known about the link between NAFLD and organochlorine pesticides (OCPs), one of the endocrine disruptors. We retrospectively analyzed the U.S. National Health and Nutrition Examination Survey 2003–2004 and compared the baseline demographics in individuals according to the presence of NAFLD (fatty liver index [FLI] ≥ 60). Logistic regression analysis was performed to determine whether OCP concentration affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The use of pesticides typically leads to the contamination of food and water systems, and they can be harmful to human health if inhaled or through occupational contact to polluted food and water. Some of the negative effects of pesticides are on the liver [ 73 , 74 ], mitochondria [ 75 ], and the heart [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of pesticides typically leads to the contamination of food and water systems, and they can be harmful to human health if inhaled or through occupational contact to polluted food and water. Some of the negative effects of pesticides are on the liver [ 73 , 74 ], mitochondria [ 75 ], and the heart [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported a correlation between exposure to pesticides such as DDT and its metabolites and metabolic disorders, including NAFLD [ 85 , 86 , 87 , 88 ], likely because the liver is the main target for these toxicants. Retrospective analysis of the U.S. National Health and Nutrition Examination Survey 2003–2004 has indicated that exposure to several OCPs, especially to oxychlordane, is strongly associated with hepatic steatosis and altered levels of hepatic enzymes [ 89 ]. Although the underlying mechanisms have not yet been fully clarified, multi-omic analysis has suggested that OCPs favor NAFLD by altering the hepatic expression of genes involved in liver steatosis, PPAR signaling and fatty acid metabolism, inflammation, and necrosis [ 90 ].…”
Section: Nutrition Environmental Pollutants and Nafldmentioning
confidence: 99%
“…Occupational or environmental exposure to different pesticides is suspected to increase the risk of developing several types of metabolic disturbances including overweight and obesity (Araújo et al 2022; Zuo et al 2022), metabolic syndrome (Lamat et al 2022), type 2 diabetes (Evangelou et al 2016; Rebouillat et al 2022) and hepatic steatosis (Sang et al 2022; Wahlang et al 2020), also referred to as fatty liver. Of note, pesticide exposure can induce liver lesions other than steatosis such as hepatic cytolysis, cholestasis and different types of vascular disorders (EASL 2019; Vilas-Boas et al 2019).…”
Section: Introductionmentioning
confidence: 99%